2019
DOI: 10.1136/bmjopen-2018-027436
|View full text |Cite
|
Sign up to set email alerts
|

Counselling-based psychosocial intervention to improve the mental health of abused pregnant women: a protocol for randomised controlled feasibility trial in a tertiary hospital in eastern Nepal

Abstract: IntroductionThe strong correlation between domestic and family violence (DFV) and mental health has been well documented in studies. Pregnancy is a period when both DFV and mental distress tend to occur and/or accentuate. Although limited, available evidence from developed countries has shown continual support and education as psychological first aid that can reduce DFV and improve mental health. However, there is significantly less number of studies from resource-constrained countries; thus, there continues t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Due to the specific psychological conditions that are experienced in DV, this strategy will play a substantial role in moderating the situation. Another item used in this model was supportive counselling, in which one of the main points of intervention was empathetic and non-judgmental listening, the same as the previous intervention mentioned above [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the specific psychological conditions that are experienced in DV, this strategy will play a substantial role in moderating the situation. Another item used in this model was supportive counselling, in which one of the main points of intervention was empathetic and non-judgmental listening, the same as the previous intervention mentioned above [17].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of a trained nurse seems to be effective in the mother's health status, personality development and, consequently, her relationship with her partner, which will in turn lead to remarkable outcomes. These include increasing listening and negotiation while disputing and reducing stress and communication regulation strategies that will reduce physical conflict [17].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, multiple promising research has shown that the average follow-up duration is six weeks. In terms of ethics, it is vital to note that women in the control group will receive a basic information packet and contact information for support (Sapkota et al, 2019), even though their level of intervention will be lower.…”
Section: Disseminationmentioning
confidence: 99%
“…A recent systematic review and meta-analysis in low-and middle-income countries by Leight et al (2023) has evidenced that group-based interventions have significantly reduced the likelihood of women experiencing IPV [32]. In sub-Saharan Africa, a number of interventions aimed at controlling and reducing IPV have been conducted [33][34][35][36], and these interventions have mostly been aimed at women. The engagement of men in interventions that target IPV prevention has been noted as crucial [37][38][39].…”
Section: Introductionmentioning
confidence: 99%